Kualitas kimia dan nilai organoleptik nugget daging itik dengan menggunakan bahan pengisi yang berbeda - Wulan Agustiani Putri; Satrio Wibowo; Lisnawaty Silitonga (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2019)
This study aims to used duck meat as a basic ingredient in making nuggets and to discover the effect of adding fillers to the chemical quality and organoleptic value of duck nuggets. This study used a fully randomized design (CRD) with four treatments and five replications, P0 (chicken nugget), P1 (duck nugget with wheat flour), P2 (duck nugget with tapioca flour), and P3 (duck nugget with corn flour). The results of this research showed that duck meat can not substitute fully replace chicken meat as the basic ingredient when making gold nuggets. Chemical quality and level of preference for nuggets with the addition of different fillers have different values. Based on the results of the study, it can be concluded that the quality of the chemical in the best treatment is achieved by the incorporation of wheat flour (P1). While in the results the organoleptic test of the preference on nuggets after chicken nugget was is duck nugget with the addition of tapioca flour (P2) in terms of aroma, texture and taste is given a higher value, although less preferred in terms of color. Keywords: Chemical quality, organoleptic value, duck nuggets, filler